Choline Supplementation Alters Some Amino Acid Concentrations with No Change in Homocysteine in Children with Cystic Fibrosis and Pancreatic Insufficiency - Alshaikh, Belal (Nutr Res, 2015)
The present study determined the plasma amino acid status in children with cystic fibrosis (CF) and pancreatic insufficiency (PI) in the modern medical and nutritional care setting and investigated the effect of choline supplementation on amino acid status. A total of 110 children, ages 5 to 18 years, with CF and PI were randomized to receive choline-enriched structured lipid (LYM-X-SORB(™), LXS) or placebo with similar calorie and fat content. Plasma amino acids were measured at baseline, 3, and 12 months. We hypothesized that choline supplementation would result in lower plasma homocysteine concentrations in children with CF. At baseline, dietary protein intake was high and the amino acid profile was within laboratory reference ranges in most subjects. Alanine and cysteine were elevated in 24% and 36% of subjects, respectively. Children with baseline alanine above reference range had improved weight, body mass index, and fat-free mass. Low homocysteine was found in 62% of children 11 years and older. After 3 and 12 months, there was no effect of choline supplementation on methionine or homocysteine status. Compared to placebo, choline supplementation resulted in increased glycine and decreased threonine, histidine, valine and total branch chained amino acids at 12 months. In conclusion, daily choline supplementation with LXS did not alter methionine-homocysteine metabolism but did result in alterations in other amino acids in children with CF and PI.